Dwarf shrub expansion and loss of lichens distinctly dominate multi-decadal changes in northern boreal understory plant communities - Tuija Maliniemi; Joonatan Lohi; Janne Alahuhta; Karoliina Huusko; Risto Virtanen (Nordia Geographical Publications)
Northern boreal forests and treelines are particularly sensitive to the current climate change that has already resulted in increased productivity, shrub expansion and up- and northward shifts of species. However, these changes are expected to be gradual or lagged due to slow process rates, and can be buffered to some extent by large herbivores. Multi-decadal observations of understory change in northern boreal forests remain scarce, particularly those involving bryophytes and lichens despite their importance for biodiversity and ecosystem functions. Here, we analyse temporal changes in understory plant communities of northern boreal forests in Saariselkä, Finland (68.46° N, 27.37° E) that were originally sampled in 1981. We resurveyed plant communities (vascular plants, bryophytes and lichens) at 22 sites (including 88 vegetation plots) in 2014 and at 80 sites (320 plots) in 2022 in different forest site types. Reindeer grazing was moderate throughout the study period (1.5–2.0 reindeer/km²), while mean annual temperature rose over 1°C. We found clear temporal shifts in plant communities towards increasing dwarf shrub dominance and decreasing lichen cover and diversity, which were consistent across the study area and within different site types. However, the increase in dwarf shrubs was species-specific: the cover of bilberry (Vaccinium myrtillus), crowberry (Empetrum nigrum) and lingonberry (Vaccinium vitis-idaea) had increased over time, while the originally most dominant species, heather (Calluna vulgaris), had decreased and become subordinate to all the above. The observed changes reflect a shift into moister conditions and are likely linked to both succession and climate change. Long-term reindeer grazing is most likely the key driver reducing lichen cover, which may be further affected by the dwarf shrub expansion. The consistency of the observed changes in different site types is indicative of corresponding changes occurring elsewhere in northern boreal forests with comparable environmental conditions and grazing pressure. Importantly, our results raise concerns about the local disappearance of lichens if the declining trend continues.